A gender-responsive breeding approach to the intensification of sesame (Sesamum indicum L.) production in the Maradi region of Niger - Lawali, Sitou; Boureima, Seyni; Idi, Salissou (Frontiers in Sociology, 2024)
Climatic variability and a decrease in soil fertility has had a detrimental effect on the productivity of the main rainfed crops in Niger (millet, sorghum, cowpea), and led to a deterioration of the nutritional status and income of the country's farmers. The spatio-temporal variability in rainfall has led rural populations to diversify their farms by integrating sesame (Sesamum indicum L.) into their cropping systems because of its low water and fertilizer requirements. Sesame is increasingly becoming a significant source of income for farmers and it contributes to their food and nutritional security. To boost the production of sesame and facilitate its rapid adoption, our breeding program focused on participatory breeding and varietal selection with the inclusion of gender-specific preferences from the variety design to the evaluation of new lines on farms. This case study shows that although women had more experience in sesame cultivation than men, they have less access to production factors such as land. This is especially problematic as recent trends in land tenure mean that the poorest are no longer able to exploit large areas of cultivable land. It also evidenced that the varietal preferences of sesame growers as well as the mastery of the production techniques are a function of the livelihoods and the investment capacity of actors in the value chain. Our study found that men mainly prefer production traits, whereas women had fewer trait preferences and their preferences tended to be relate to marketing and processing. This highlights the contrasting roles and responsibilities between men and women in the sesame value chain. Therefore, inclusion of complementary women's and men's preferred traits, provided they are not negatively correlated with a variety profile, will help meet the full range of needs across the value chain. We recommend the inclusion of gender research in setting breeding goals prior to variety design.